KENDALA-KENDALA YANG DIHADAPI MAHASISWA SOSIOLOGI DALAM MELAKSANAKAN PROGRAM PENGALAMAN LAPANGAN KEPENDIDIKAN (PPLK) PERIODE JULI-DESEMBER 2012 DI SMA PERTIWI 2 PADANG - Gusman, Diana; Adiyalmon, Adiyalmon; Husnita, Liza (Pendidikan Sosiologi, 2013)
One of the compulsory subjects of STKIP PGRI is subject of educational field practice which known as Praktek Lapangan Kependidikan (PLK) that its goal is to make students have ability to utilize knowledge that has been studied in real situation on teaching activity and non-teaching activity at the practicing school, so that students get experience in teaching. Every students who will participate in PLK are provided with variety of knowledge and skill firs, which is appripriate with competence. However, in reality, based on authorâs observation in SMA Pertiwi 2 Padang about realization of PPLK of STKIP PGRI Sumbar in period of Juli-December 2012, author found many problems faced by PPLK students. Purpose of this research is to reveal : 1). Contraints faced by Sociology student when practice teaching in SMA Pertiwi 2 Padang, 2). Tutor teacherâs effort in overcoming constraints faced by Sociology students in PPLK at SMA Pertiwi 2 Padang.This reasearch is done by qualitative approach and descriptive type. The selection of informants of this research was done by purposive sampling, informants of this research were six person which 4 persons are Sociology students and 2 persons were teachers tutor of Sociology subjeck. The data of this research were primary data and secondary data. Primary data was all the data obtained from the informants of research, and secondary data was all the data obtained from school as support such as dokuments rule, the data of teachers and students, reading book and RPP. The technique of data colection in this research were the us of interview technique, observation and documentary. All data obtained were processed and analized by using Trianggulation technique through several phases : data collection phase, data reduction, data presentation, and drawing conclusion process.The result of this reseach revealed that : 1). Constraints faced by Sociology students in PPLK at SMA Pertiwi 2 Padang were : a). Lack of ability in construct learning device or RPP, b). Lack of ability in mastering teaching material, c). Lack of ability to apply basit skill of teaching, 2). An effort from the tutor-teacher in overcoming constraints faced by sociology students in implementing PPLK at SMA Pertiwi 2 Padang, as follow : a). Provide examples or guidance to students about how to construct RPP, b). Provide guidance and instruction to every students who will do teaching learning process in classroom, c). Notify the students about the idicators that should be given to students, d). Give instructions to the students about how the implementation of teaching and learning process in the classroom.